2004
DOI: 10.1016/s1074-7613(04)00103-7
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Blood-Borne CD8 Memory T Cell Migration In Vivo

Abstract: Memory T cells are distributed throughout the body following infection, but the migratory dynamics of the memory pool in vivo is unknown. The ability of circulating microbe-specific memory T cells to populate lymphoid and nonlymphoid tissues was examined using adoptive transfer and parabiosis systems. While migration of memory CD8 T cells to lymph nodes and peritoneal cavity required G(i)-coupled receptor signaling, migration to the spleen, bone marrow, lung, and liver was independent of this pathway. Followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
363
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 345 publications
(394 citation statements)
references
References 65 publications
26
363
0
1
Order By: Relevance
“…As suggested by findings in recent publications (10,11), this population of peripheral memory CD4 ϩ T cells would localize to the lung parenchyma (and other peripheral sites) following primary immunization with the RSV G-expressing vaccinia vector and could potentially respond to challenge RSV infection in situ (i.e., in the infected lungs). Alternately, these findings could also be explained by a mechanism whereby G-specific memory CD4 ϩ V␤14 ϩ T cells present in the recirculating T cell pool would enter the draining PBLN and activate in the PBLN in response to RSV infection.…”
Section: Activation Of Resting G-specific Memory Cd4 ϩ T Cell Precursmentioning
confidence: 84%
“…As suggested by findings in recent publications (10,11), this population of peripheral memory CD4 ϩ T cells would localize to the lung parenchyma (and other peripheral sites) following primary immunization with the RSV G-expressing vaccinia vector and could potentially respond to challenge RSV infection in situ (i.e., in the infected lungs). Alternately, these findings could also be explained by a mechanism whereby G-specific memory CD4 ϩ V␤14 ϩ T cells present in the recirculating T cell pool would enter the draining PBLN and activate in the PBLN in response to RSV infection.…”
Section: Activation Of Resting G-specific Memory Cd4 ϩ T Cell Precursmentioning
confidence: 84%
“…This view was in contrast with the largely accepted notion at the time that recirculating memory T cells are maintained by a homeostatic equilibrium between proliferation and death long after antigen clearance 2 . Furthermore, it did not accommodate previous data concerning the proliferation 3,4 and recirculation 5,6 of memory CD8 + T cells in the bone marrow.…”
Section: Francesca DI Rosamentioning
confidence: 62%
“…Moreover, global transcription data, CD69 expression profiles and colocalization in tissue sections do not address in vivo T cell migration. In fact, in situ-labelling studies and parabiosis experi ments have shown that memory T cells do recirculate to and from the bone marrow 5,6 .In conclusion, the available evidence supports the view that the bone marrow is a 'stopping point' where recirculating memory CD8 + T cells are stimulated to proliferate before continuing to move around the body 3,4,12,13 . Notably, lodging into the bone marrow is a competitive process among memory T cells 14 , which is an element to be considered especially in interpretation of adoptive transfer data 11,14 .…”
mentioning
confidence: 60%
See 1 more Smart Citation
“…T RM have been found in several tissues, including the skin, gut, lung and brain [3][4][5][6]. Once established, T RM are maintained independently of circulating T EM and T CM and their presence correlates with superior protection against local viral challenge [3,5,7]. However, the exact role of T RM vs. recruited circulating memory T cells in controlling viral replication is unclear.…”
Section: Tissue-resident Memory T Cells (T Rmmentioning
confidence: 99%